2016
DOI: 10.1097/txd.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

The Kupffer Cell Number Affects the Outcome of Living Donor Liver Transplantation from Elderly Donors

Abstract: BackgroundThere have been no previous reports how Kupffer cells affect the outcome of living donor liver transplantation (LDLT) with an elderly donor. The aim of this study was to elucidate the influence of Kupffer cells on LDLT.MethodsA total of 161 adult recipients underwent LDLT. The graft survival, prognostic factors for survival, and graft failure after LDLT were examined between cases with a young donor (<50, n = 112) and an elderly donor (≥50, N = 49). The Kupffer cells, represented by CD68-positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…The poor outcome with the older donor age group in our study may be attributed to the effect of aging on the liver’s capacity for regeneration . Hidaka et al have attributed that to the significantly fewer Kupffer cells in liver grafts donated from elderly donors than those procured from young donors . They reported that the low Kupffer cell number in elderly liver grafts (>50 years) was a prognostic factor for graft failure after LDLT .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The poor outcome with the older donor age group in our study may be attributed to the effect of aging on the liver’s capacity for regeneration . Hidaka et al have attributed that to the significantly fewer Kupffer cells in liver grafts donated from elderly donors than those procured from young donors . They reported that the low Kupffer cell number in elderly liver grafts (>50 years) was a prognostic factor for graft failure after LDLT .…”
Section: Discussionmentioning
confidence: 56%
“…(31) They reported that the low Kupffer cell number in elderly liver grafts (>50 years) was a prognostic factor for graft failure after LDLT. (31) Regarding gene senescence and liver regeneration, Eguchi et al reported that there was no graft rejuvenation in pediatric recipients when grafts from old donors had been used in LDLT. (32) They assessed the transplanted grafts for the expression of the senescence marker protein-30 (SMP-30), which is correlated to hepatocyte proliferation, a decrease of reactive oxygen species, and exertion of a cytoprotective function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KC treated with gadolinium chloride prevented the induction of portal venous tolerance by inhibiting Ag presentation to lymphocytes, supporting the notion that both Ag presentation to and stimulation of lymphocyte proliferation are necessary for tolerance induction (17). In human studies, a greater number of KC typically found in younger living donors predicts better hepatic allograft survival compared to elderly living donors, suggesting that KC in the donor liver are a relevant prognostic factor influencing post-transplant outcomes (18). Graft-infiltrating DC and KC were also shown to be increased during and after rat liver transplant tolerance induction, again suggesting a possible important role for these cells in shaping the host immune response toward tolerance (19).…”
Section: Intrahepatic Immune Cells Interact With Liver Parenchymal Cementioning
confidence: 62%
“…Kupffer cell number is restored to its initial level after Kupffer cell depletion [ 29 , 30 ]. Also, a high Kupffer cell number increases patient survival rates following liver transplantation [ 31 ], and alterations in Kupffer cell number are associated with specific liver pathologies [ 32 ], although distinguishing bona fide Kupffer cells from infiltrating monocytes and monocyte-derived macrophages is challenging. Akin to other macrophage populations, Kupffer cells were long believed to lack the ability to proliferate [ 33 ], and monocytes were thought to be their sole source for replenishment [ 34 ].…”
Section: Self-renewal Ability Of Kupffer Cellsmentioning
confidence: 99%